Manajemen Manajemen strategi operasional pada lembaga keuangan mikro syariah dalam meningkatkan keberlanjutan usaha - Aini, Mufidatul (Maliki Interdisciplinary Journal, 2025)
Islamic Microfinance Institutions (LKMS) play a crucial role in promoting community-based economic growth through a financial system founded on the principles of justice, transparency, and social welfare. This study aims to analyze the implementation of operational strategy management in LKMS to enhance business sustainability. The research employs a literature review method by examining relevant academic journals and scientific publications related to strategic management, operational efficiency, and institutional sustainability. The findings indicate that the success of LKMS operational strategies depends on the institution’s ability to manage efficiency, optimize human resources, and apply innovation through digital-based services. Operational efficiency helps reduce costs and improve productivity, while human resource development through technical and spiritual training contributes to better service quality. Moreover, innovation and digital transformation in financing systems accelerate administrative processes and expand service accessibility. Entrepreneurial assistance for clients also serves as a vital component to ensure productive and sustainable use of financing funds. Socioeconomic conditions, governance, and compliance with Islamic principles are key factors that influence the long-term sustainability of LKMS in a dynamic business environment. With adaptive, efficient, and sharia-compliant operational strategies, LKMS can strengthen competitiveness, increase public trust, and contribute to the realization of a sustainable Islamic economic system.